Øyvind Østerud, Agrarian Structure and Peasant Politics in Scandinavia. A Comparative Study of Rural Response to Economic Change, Oslo: Universitetsforlaget, 1978, 279 s., 75,00 n.kr. - Elklit, Jørgen (Politica, 1979)
-